Economic development of Burma - "Hagen, Everett E." (Washington, 1956)
This report is the third in a series of studies of the economic development problems and prospects of individual noncommunist countries considered within the broader context of their political, social, and cultural institutions. The NPA International Committee is sponsoring these reports to help improve American understanding of the complexities of the development process and to make better known the various techniques which have been de vised and tested for stimulating a country's economic growth. The effectiveness of American cooperation with the peoples of Latin America, southern Asia, and Africa depends directly upon the quality of our and their under standing of the problems they face in seeking to improve their conditions of life in ways consistent with the achievement and preservation of freedom and democracy every where in the world. Inadequate understanding of problems and possibilities is one of the most important human obstacles to economic and political progress. It is our hope that through fostering better knowledge these NPA re ports can make a significant contribution to greater co operation between the American people and our friends in Latin America, southern Asia, and Africa to the mutual advantage of all free nations.
Keywords: Economics